(untitled) (Bangladesh Agronomy Journal, 2021)
Screening of improve varieties for new areas is necessary to address the soil and environment for improving crop production systems. In this context, six separate field trials were conducted at farmer’s field in Sylhet areas for the two consecutive crop seasons during 2017-18 and 2018-19, respectively to evaluate the performance of improved varieties of crops with the existing cultivars. Each experiment was laid out in randomized complete block design with six dispersed replications. The unit plot size was varied with experiments. The result showed that improved varieties of oilseed crops mustard var. BARI Sarisha-16, soybean var. BARI Soybean-6, groundnut var. BARI Chinabadam-9, sesame var. BARI Til-4 and sunflower var. BARI Surjomukhi-2 performed better under the soil and climatic conditions of Sylhet region. This result reveled that these varieties of oilseed crops could be suitable for higher productivity and economic return. Bangladesh Agron. J. 2020, 23(2): 87-95